Hepatic histological findings in suspected drug‐induced liver injury: Systematic evaluation and clinical associations. Issue 2 (18th December 2013) - Kleiner, David E.; Chalasani, Naga P.; Lee, William M.; Fontana, Robert J.; Bonkovsky, Herbert L.; Watkins, Paul B.; Hayashi, Paul H.; Davern, Timothy J.; Navarro, Victor; Reddy, Rajender; Talwalkar, Jayant A.; Stolz, Andrew; et al.
<x xml:space="preserve">Abstract</x> Drug‐induced liver injury (DILI) is considered to be a diagnosis of exclusion. Liver biopsy may contribute to diagnostic accuracy, but the histological features of DILI and their relationship to biochemical parameters and outcomes are not well defined. We have classified the pathological pattern of liver injury and systematically evaluated histological changes in liver biopsies obtained from 249 patients with suspected DILI enrolled in the prospective, observational study conducted by the Drug Induced Liver Injury Network. Histological features were analyzed for their frequency within different clinical phenotypes of liver injury and to identify associations between clinical and laboratory findings and histological features. The most common histological patterns were acute (21%) and chronic hepatitis (14%), acute (9%) and chronic cholestasis (10%), and cholestatic hepatitis (29%). Liver histology from 128 patients presenting with hepatocellular injury had more severe inflammation, necrosis, and apoptosis and more frequently demonstrated lobular disarray, rosette formation, and hemorrhage than those with cholestasis. Conversely, histology of the 73 patients with cholestatic injury more often demonstrated bile plugs and duct paucity. Severe or fatal hepatic injury in 46 patients was associated with higher degrees of necrosis, fibrosis stage, microvesicular steatosis, and ductular reaction among other findings, whereas eosinophils and granulomas were found more often in those with milder injury. Conclusion: We describe an approach for evaluating liver histology in DILI and demonstrate numerous associations between pathological findings and clinical presentations that may serve as a foundation for future studies correlating DILI pathology with its causality and outcome. (Hepatology 2014;59:661–670)